Pacific community’s perceptions on how to improve uptake of urate-lowering therapy for Pacific gout patients - Samuela Ofanoa; Malakai Ofanoa; Siobhan Tu’akoi; Hinamaha Lutui; Maryann Heather; Felicity Goodyear-Smith (International Journal for Equity in Health)
Abstract Objectives This study aims to explore the views of Pacific people on how to improve the management of urate-lowering therapy among Pacific gout patients in South Auckland. Methods The study used the Fa’afaletui model to explore the views on gout management across different perspectives of Pacific community members and health professionals working in health providers with high Pacific patient populations. Three workshops were delivered with the community and health professionals. All data were collected by note-takers and analysed using a general inductive approach. Participants were given the opportunity to review the results of the previous workshop before starting the next one. Results The key findings from this study clustered into three key themes: [1] Gout interventions guided by Pacific frameworks and research; [2] a multifaceted approach including education, improved access to treatment and screening for gout, and strategies to help Pacific gout patients remain engaged and adherent; and [3] Pacific gout champions. Conclusion This study presents the views of community members of how to improve the uptake of urate-lowering therapy among Pacific gout patients. The community highlighted the need for a multifaceted intervention governed by a Pacific model, addressing access barriers and education for Pacific gout patients.